Knowledge, Attitudes, and Practices Concerning Water, Sanitation, and Hygiene and Related Diseases Among University Students in Malaysia - Jeffrey, Renee Ng; Shamsuddin, Aida Soraya; Ariffin, Farah Diyana; Zulkifli, Aziemah (UI Scholars Hub, 2025)
Background: Water, sanitation, and hygiene (WASH) practices are fundamental components of public health, being crucial in preventing disease transmission and promoting healthy living environments. In this context, university students play an essential role as future professionals and community advocates in fostering proper hygiene behaviors and preventing disease outbreaks. Understanding knowledge, attitudes, and practices (KAP) in regard to WASH among individuals, particularly university students, is crucial for promoting proper hygiene behaviors. This study aimed to assess the KAP in regard to WASH and related diseases among undergraduate students from the Faculty of Health Sciences, Universiti Kebangsaan Malaysia (UKM). Methods: A cross-sectional study was conducted using a structured online questionnaire distributed via email. A total of 214 students participated in and completed the questionnaire. Results: About 90.2% (N = 193) of the respondents demonstrated good knowledge, 69.2% (N = 148) showed positive attitudes, and 80.4% (N = 172) exhibited good practices concerning WASH. Weak but positive correlations were observed between the knowledge and practice scores (r = 0.205, p < 0.01) and between the attitude and practice scores (r = 0.376, p < 0.01). Conclusions: These findings highlight the need to strengthen WASH education in higher education institutions, particularly within health sciences programmes, through a more comprehensive and holistic approach.